Sei sulla pagina 1di 6

# www.urdulovers123.blogspot.

com

Khanewal

## Exercise 2.4 (Solutions)

Question # 1 (i)
1- x
y =
1+ x
1- x
Put u =
1+ x

Let

(1 + x )( -1) - (1 - x )(1)
2
(1 + x )
2

du
-2
=
2
dx
(1 + x )
Now diff. y w.r.t. u
dy
d 12
=
u
du
du
1 -1
1 1- x
= u 2 =

2
2 1+ x
dy
1 1+ x
=

du
2 1- x
Now by chain rule
dy
dy du
=

dx
du dx

-1

1
2

=
=

1
2

(1 + x ) -1
1
2
(1 - x ) 2 (1 + x )
-1

(1 - x ) (1 + x )
1
2

-1
1 - x (1 + x )

Question # 1(ii)
y =

dy
1
=
du
2 x+ x
Now by chain rule
dy
dy du
=

dx
du dx
1
2 x +1
=

2 x
2 x+ x
=

1 1+ x 2
-2
=

2 1 - x (1 + x )2
=

1
2

y = u = u2
Diff. u w.r.t. x
1
du
d
2
=
x
+
x

dx
dx

1
1 1
= 1+ x 2 = 1+
2
2 x
2 x +1
=
2 x
Now diff. y w.r.t. x
dy
d 12
=
u
du
du
1 -1
1
1
= u 2 =
=
1
2
2u 2
2 x+ x

-1 - x - 1 + x

(1 + x )

u = x + x = x + x2
1

So y = u
y = u2
Now diff. u w.r.t. u
du
d 1- x
=

dx
dx 1 + x
d
d
(1 + x ) (1 - x ) - (1 - x ) (1 + x )
dx
dx
=
2
(1 + x )
=

FSc-II / Ex 2.4 - 1

x+ x

3
2

2 - 12

2 x +1

4 x x+ x

Question # 1 (iii)
a+x
y = x
a-x
a+x
Put
u =
a-x
1

So
y = x u = x (u ) 2
Diff. w.r.t. x
1
dy
d
=
x (u ) 2
dx
dx
1
1 d
d
= x (u ) 2 + ( u ) 2
x
dx
dx
1
1 - 1 du
= x (u ) 2
+ ( u ) 2 (1)
2
dx
1
1
dy
x
- du

= (u ) 2
+ ( u ) 2 . (i)
dx
2
dx
Now diff. u w.r.t. x

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link

www.urdulovers123.blogspot.com

FSc-II / Ex 2.4 - 2

du
d a+x
=

dx
dx a - x
d
d
(a - x) (a + x) - (a + x) (a - x)
dx
dx
=
2
(a - x)
=
=
=

( a - x )( 0 + 1) - ( a + x )( 0 - 1)
2
(a - x)
( a - x )(1) - ( a + x )( -1)
2
(a - x)
a-x+a+x

(a - x)

## Using value of u and

dy
xa+ x
=

dx
2 a - x

-1

2a

(a - x)

du
in eq. (i)
dx
1

2a

( a - x )2

a + x 2
+

a-x

-1

1
2

(a + x) (a - x)

2- 1

Question # 2(iv)
4 x 2 + 2hxy + by 2 + 2 gx + 2 fy + c = 0
Differentiating w.r.t. x

( a - x)2

( a + x)2
+
3
1
1
(a + x ) 2 (a - x )2 (a - x )2
ax + (a + x )(a - x)

dy
=
dx

(a + x) 2 (a - x)2
3

ax + a 2 - x 2
1

(a + x) 2 (a - x)2

## Question # 1 (iv) & (v)

Do yourself as above
Question # 2 (i)
3x + 4 y + 7 = 0
Diff. w.r.t. x .
d
d
( 3x + 4 y + 7 ) = (0)
dx
dx
dy
3(1) + 4 + 0 = 0
dx
dy
dy
3
4
= -3
= dx
dx
4

Question # 2 (iii)
Do yourself

(a + x )2

ax

( a + x ) 2 ax + ( a + x ) 2
1
2
-1
(a - x) 2 (a - x) (a - x)2
ax

Question # 2 (ii)
xy + y 2 = 2
Differentiating w.r.t. x
d
d
xy + y 2 =
( 2)
dx
dx
d
d

( xy ) + y 2 = 0
dx
dx
dy
dx
dy
x + y + 2y
= 0
dx
dx
dx
dy
( x + 2 y ) + y (1) = 0
dx
dy
(x + 2y) = - y
dx
dy
(x + 2y) = - y
dx
dy
-y

=
dx x + 2 y

(4x
dx
d

+ 2hxy + by 2 + 2 gx + 2 fy + c =

d
dx

(0)

d 2
d
d
( x ) + 2h ( xy ) + b ( y 2 )
dx
dx
dx
d
d
d
+2 g ( x ) + 2 f
( y ) + ( c) = 0
dx
dx
dx
dy
dy

4(2 x) + 2h x + y (1) + b 2 y
dx
dx

dy
+2 g (1) + 2 f
+0 = 0
dx
dy
dy
8 x + 2hx + 2hy + 2by
dx
dx
dy
+2 g + 2 f
= 0
dx
4

2 ( hx + by + f )

dy
dx

+ 2 ( 4 x + hy + + g ) = 0

dy
= - 2 ( 4 x + hy + + g )
dx
dy
( hx + by + f ) = - ( 4 x + hy + + g )
dx
dy
4 x + hy + + g

= dx
hx + by + f
2 ( hx + by + f )

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link

www.urdulovers123.blogspot.com

FSc-II / Ex 2.4 - 3

Question # 2 (v)

x (1 + y ) 2 + y (1 + x ) 2 = 0
1

x 1+ y + y 1+ x = 0
Differentiating w.r.t. x

1
1
d
d
d
x (1 + y ) 2 +
y (1 + x ) 2 =
(0)
dx
dx
dx

1
1 dx
1
1 dy
d
d
(1 + y ) 2 + (1 + y ) 2 + y (1 + x ) 2 + (1 + x ) 2 = 0
dx
dx
dx
dx
1
1
1
1 dy
1
1
- dy
x (1 + y ) 2
+ (1 + y ) 2 (1) + y (1 + x ) 2 (1) + (1 + x ) 2
= 0
2
dx
2
dx
1
1 dy
x
dy
y
2 +
2

+
+
1
y
+
1
+
x
= 0
(
)
(
)
1
1
dx
dx
2
2
2 (1 + y )
2 (1 + x )

1 dy
1
y
x
2
2

= - (1 + y ) +
1 + (1 + x )
1
2 (1 + y ) 2
dx

2 (1 + x ) 2

x + 2 (1 + x ) 12 (1 + y ) 12 dy
2 (1 + x ) 12 (1 + y ) 12 + y

= -
1
1
dx

2
2
2
1
+
2
1
y
+
x
(
)
(
)

x + 2 (1 + x)(1 + y ) dy
2 (1 + x)(1 + y ) + y

=

2 1+ y
2 1+ x

dx

2 (1 + x)(1 + y ) + y
2 1+ y
dy

=
dx
2 1+ x
x + 2 (1 + x )(1 + y )

(
(

1 + y 2 (1 + x)(1 + y ) + y
dy
= dx
1 + x x + 2 (1 + x)(1 + y )

)
)

Question # 2 (vi)

y x2 - 1 = x x2 + 4
Differentiating w.r.t x
1
d
d
2
2
y x -1 =
x x +4 2
dx
dx
1
1
d 2
dy
d 2
dx
2
2
2
y
x -1 + x -1
=x
x +4 + x +4 2
dx
dx
dx
dx
1
1
dy
1
y ( 2x ) + x2 -1
= x x 2 + 4 2 (2 x ) + x 2 + 4 2 (1)
dx
2
1
dy
x2
2
2
2
2 xy + x - 1
=
+
x
+
4
1
dx
x2 + 4 2

) (

dy
x2
x -1
=
dx
x2 + 4

dy
x2
x -1
=
dx
x2 + 4

(
(

)
)

1
2

) (

1
2

1
2

+ x +4

1
2

- 2 xy
- 2 xy

2
2
2
dy x + x + 4 - 2 xy x + 4
x -1
=
1
dx
x2 + 4 2
2

+ x +4

2
2
dy 2 x + 4 - 2 xy x + 4
=
dx
x2 -1 x2 + 4

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link

www.urdulovers123.blogspot.com

FSc-II / Ex 2.4 - 4

Question # 3 (i)
1
Since x = q +
q
x = q + q -1
Differentiating x w.r.t. q
dx
d
=
q + q -1
dq
dq

=
=

1
q -1
=
2
q
q2
2

dq
q2

= 2
dx
q -1
Now y = q + 1
Diff. w.r.t. q
dy
d
dy
=
= 1
(q + 1)
dq
dq
dq
Now by chain rule
dy
dy dq
=

dx
dq dx
dy dq
q2
=

= 1 2
dq dx
q -1

= a

) (

) (

) (

( )
) ( -2t ) - (1 - t ) ( 2t )
(1 + t )

2 2

2b + 2bt 2 - 4bt 2

1+ t2

2b 1 - t 2

(1 + t )

2b - 2bt 2

(1 + t )

2 2

2 2

2b 1 - t 2

) (1 + t )

2 2

(1 + t ) - 4at
b (1 - t )
= 2 2

2at

(1 + t )

2 2

2bt
y
1+ t2
Diff. w.r.t. t
Now y =

dy
d 2bt
=

dt
dt 1 + t 2

## Now by chain rule

dy
dy dt
=

dx
dt dx

-2t - 2t 3 - 2t + 2t 3

dx
- 4at
dt

=
2
2
dt
dx
1+ t

Question # 4
1- t2
Since x =
1+ t2
Differentiating w.r.t. t , we get (solve
yourself as above)
dx
- 4t
dt
1+ t2
=

=
dt
1+ t2
dx
- 4t
2bt
Now y =
1+ t2
Differentiating w.r.t. t , we get (solve
yourself as above)
2 1- t2
dy
=
2
dt
1+ t2

2 2

dy
dx

dy
q
= 2
dx
q -1

## Now by chain rule

dy
dy dt
=

dx
dt dx

Question # 3 (ii)
a 1- t2
Since x =
*Correction
1+ t2
Diff. w.r.t. t
dx
d 1- t2
= a

dt
dt 1 + t 2
d
d
1+ t2
1- t2 - 1- t2
1+ t2
dt
dt
= a
2
2
1+ t

(1 + t
a

= 1 - q -2 = 1 -

## (1 + t ) dtd 2bt - 2bt dtd (1 + t )

(1 + t )
(1 + t ) 2b(1) - 2bt ( 2t )
(1 + t )

(1 + t )

2 2

- 4at

2 1- t2

1+ t2

) (1 + t )

2 2

- 4t

dy
1- t2
= dx
2t
Multiplying both sides by y

dy
1- t2
y
= -y
dx
2t
2t 1 - t 2
=
1 + t 2 2t

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link

www.urdulovers123.blogspot.com

dy
1- t2
= dx
1+ t2
dy
y
= -x
dx
dy
y
+x = 0
dx

du
d 2
=
x
dx
dx

1- t2
Q x =
1+ t2
Proved.

Question # 5(i)
1
Suppose y = x 2 - 2 and u = x 4
x
Diff. y w.r.t x
dy
d 2 1
=
x - 2
dx
dx
x
d 2
=
x - x -2 = 2 x + 2 x -3
dx
1

= 2 x + 3
x

4
x +1
dy

= 2 3
dx
x
Now diff. u w.r.t x
du
d 4
=
x
dx
dx
du

= 4 x3
dx
Now by chain rule
dy
dy dx
=

du
dx du
dy 1
=

dx du
dx
4
x +1 1
dy

= 2 3 3
du
x 4x

( )

= 2x

Differentiation y w.r.t x
n
dy
d
=
1 + x2
dx
dx
n -1 d
1 + x2
= n 1 + x2
dx

dy d x 2 + 1
=

dx dx x 2 - 1
= Solve yourself =

=
=

( ) (
n (1 + x ) ( 2 x )
2nx (1 + x )
2 n -1

2 n -1

- 4x
x2 - 1

## Now diff. u w.r.t x

du
d x -1
=

dx
dx x + 1
2

= Solve yourself =

( x + 1)

du
( x + 1)

=
dx
2
Now by chain rule
dy
dy dx
=

du
dx du

Question # 5 (iii)
x2 + 1
x -1
Let y = 2
and u =
x -1
x +1
Diff. y w.r.t x

Question # 4(ii)

and u = x 2

dx 1
=
du 2 x

dy
x +1
=
du
2 x6

## Now by chain rule

dy
dy dx
=

du
dx du
n -1 1
dy

= 2nx 1 + x 2

du
2x
n -1
dy

= n 1 + x2
du

Let y = 1 + x 2

FSc-II / Ex 2.4 - 5

- 4 x ( x + 1)

2
x2 - 1

- 2x
2
( x + 1)
( x - 1) ( x + 1)

- 2 x ( x + 1)
dy
=
dx
( x - 1)

Question # 5(iv)
ax + b
ax 2 + b
Let y =
and u = 2
cx + d
ax + d
Diff. y w.r.t. x
dy d ax + b
=

dx dx cx + d

## Now differentiating u w.r.t x

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link

www.urdulovers123.blogspot.com

FSc-II / Ex 2.4 - 6

d
dx

d
dx

( cx + d ) ( ax + b ) - ( ax + b ) ( cx + d )
( cx + d )2

( cx + d )( a ) - ( ax + b )( c )
2
( cx + d )

acx + ad - acx - bc

( cx + d )

dy
=
dx

( cx + d )

## Now diff. u w.r.t x

du
d ax 2 + b
=

dx
dx ax 2 + d
=

du d 3
=
x
dx dx
= 3x 2
dx
1

= 2
du 3 x
Now by chain rule
dy
dy dx
=

du
dx du
- 4x
1
=
2
2
x2 - 1 3x

dy
-4
=
dx
3x x 2 - 1

d (ax 2 + b) - ( ax 2 + b ) d ( ax 2 + d )
( ax 2 + d ) dx
dx

=
=

( ax

( ax

+d

( ax

( ax

+d

2ax ( d - b )
2

+d

( ax

+d

+d

dx
=
du
2ax ( d - b )
Now by chain rule
dy
dy dx
=

du
dx du

+ d ( 2ax ) - ax 2 + b ( 2ax )

2ax ax 2 + d - ax 2 - b

( ax

( cx + d )

( ax

+d

2ax ( d - b )

( ad - bc ) ax 2 + d
dy
=
2
dx
2ax ( cx + d ) ( d - b )
2

Question # 5 (v)
x2 + 1
Let y = 2
and u = x 3
x -1
Diff. y w.r.t x
dy d x 2 + 1
=

dx dx x 2 - 1
= Solve yourself
- 4x
=
2
x2 - 1

## Now diff. u w.r.t x

Math, Physics, Chemistry And Other Study Notes Freely Available Below Link